The Refugee Convention in the 21st Century - Glazebrook, Susan (Victoria University of Wellington Law Review, 2018)
Over the last decade a series of humanitarian crises such as the Syrian conflict has seen an explosion in the number of refugees and internally displaced persons around the world. The resulting unprecedented movement of people has placed a strain on the 1951 Convention relating to the Status of Refugees. This article discusses the operation of the Convention in the 21st century, with a particular focus on the position of women and children. It analyses whether the Convention is adequately protecting the needs of the world's refugees in light of the current crises and other challenges such as climate change. Alternative international initiatives are also discussed.